UTILIZATION OF ARECA NUT (Areca catechu L.) SHELL WASTE FOR CELLULOSE ACETATE MEMBRANES - Bhernama, Bhayu Gita; Hulwah Nadhila; Jihan Amalia; Febrina Arfi; Muammar Yulian (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The skin of the betel nut contains 65.8% cellulose, the seeds of the fruit contain 53.20% cellulose fiber. The aim of the research is to synthesize cellulose acetate membranes from betel nut shell waste. The research method was cellulose isolation using soxhletation, bleaching, delignification and hydrolysis methods, synthesis of cellulose acetate and cellulose acetate membranes with variations of 9 and 10% PEG. The cellulose content of banana peel is 28.09% with β cellulose type and monoclinic crystal form. The tensile test results for PEG 9% were 1.4437 Mpa and PEG 10% were 1.2429 Mpa. The swelling test results of PEG 9% were 150.7% and PEG 10% were 196%. It was concluded that betel nut shell waste can be synthesized into cellulose acetate membranes.